Efektivitas Metode Jigsaw pada Peserta Didik Abad 21 - Sukmawati, Anis; Khamalia, Novi Aghata Nur; Zuhroh, Nur Elvinatuz (TSAQOFAH, 2023)
This study aims to find out more about the application of learning methods which is one of the factors for success in learning from a person. The research method used in this scientific paper is the method of content analysis and literature review. The writing results show that the jigsaw method can be applied in the learning process in the 21st century as an alternative to creating a fun learning atmosphere. The jigsaw method is basically a method that is applied so that students can have a sense of cooperation to achieve good things. There are steps that must be taken in applying the jigsaw method in order to get good and perfect results. In this method, there are advantages and disadvantages that can be used as material for consideration in the learning process.